(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Background: Staphylococcus aureus is a nosocomial bacterium that causes different kind of diseases, including urinary tract infections., skin infection, meningitis, wound infection, pneumonia and septicemia. The development of vancomycin-resistant Staphylococcus aureus, encoded by the VanA gene, is caused by the spread of Staphylococcus aureus among patients.. The aim of present study is to get the rates of Staphylococcus aureus infections and to detect vancomycin resistant gene in Staphylococcus aureus isolated from different clinical samples. Material and Methods: A total of 175 isolates of S. aureus were collected from different clinical samples including patients attending public hospitals during a period from April 2020 to December 2020. Identification was done depending on biochemical test, Vitek compact system. Vancomycin susceptibility test was done for each sample. Results: The rate of Staphylococcus aureus infections in different specimens were as following: nasal swabs (28%), wound swab (22.8%), urine (26.9%), biopsy (6.3%), sputum (9.1%) and HVS (6.85%). The rate of vancomycin resistance was (10.3%) by vitek 2 system. All Staphylococcus aureus isolates were subjected for vancomycin resistance gene by means of increasing of VanA gene by polymerase chain reaction technique (PCR), the vancomycin resistant gene size is (732 bp), in which (13.7%) of isolates represented vancomycin resistant gene positive. Conclusion: Detection of Vancomycin resistant gene by PCR shows higher sensitivity and specificity than other methods.